Comparative Influence of Hydrometeorological Processes on the Interannual Variability of Seasonal Fluctuations of the Baltic Sea Level - Zakharchuk Eugenii; Vinogradov Mihail; Sukhachev Vladimir; Tihonova Natal'ya Aleksandrovna (Russian Journal of Earth Sciences, 2024)
With the help of long-term average daily tide gauge observations of sea level, satellite altimetry measurements and data from reanalyses of meteorological and hydrophysical fields, the features and physical mechanisms of interannual variability of seasonal fluctuations in the level of the Baltic Sea are investigated. It is shown that for the period 1889-2022 in Stockholm, in interannual changes in the amplitudes of harmonics Sa, Ssa, Sta, Sqa, there are statistically insignificant positive linear trends, against the background of which long-term cycles with time scales approximately from 20–35 to 55 years and very significant changes in amplitudes from 0.5–1.0 to 25–27 centimeters are observed. In recent decades, the harmonics Sa, Ssa, and Sta have seen a noticeable decrease in the amplitudes and dispersion of oscillations. The results of mutual correlation and multiple regression analyses of anomalies of seasonal fluctuations in sea level and various hydrometeorological processes indicate that the largest contribution to the interannual variability of seasonal fluctuations in sea level is made by changes in the tangential friction of the wind. The second most important processes are changes in atmospheric pressure over the sea and water exchange between the Baltic and North Seas. Changes in freshwater balance and density have the smallest impact on interannual variability in seasonal sea-level patterns.